Compositional strategies and effectiveness of 6th grade students in relation to teaching - Arbiol Solaz, Amelia; Paulo Noguera, Mar (Didáctica. Lengua y Literatura, 2016)
From the 70s, the teaching and learning strategies for writing development as a communicative tool and transformation of knowledge have become an issue in K12 education. Actually, many students show expression difficulties, and they are not always able to overcome them. Therefore, despite the time elapsed, we still need to analyse educational practice and the impact on learning of writing. Our research about classroom practices analyses educational strategies regarding the teaching and learning of writing skills and its impact over the acquisition of compositional strategies and over their effectiveness in 6th grade students. It is a comprehensive-interpretative research through reflection about improving teaching skills and effectiveness in students writing techniques.
Keywords: Teaching and learning of written composition; classroom activity; compositional strategies; metadiscursive; metalinguistic and metacognitive reflection; and compositional effectiveness.